Effect of different soil moisture content on physiological and agronomical characteristics of newly developed upland rice varieties - BLEOUSSI, Tchèlissa Myriam Roseline; BOKOSSA YAOU, Innocent Padonou; FOFANA, Mamadou; MENSAH, GUY APOLLINAIRE; TCHEKESSI, C. K. Célestin; SACHI, Pivot S. A.; DJOGBE, Anayce; BANON, Jultesse (My University, 2016)
Water deficit is one of the environmental factors that cause a great reduction in the upland rice grain yield. The objective of this study was to access the morpho-physiological responses of some newly developed upland rice varieties (NERICA 1, NERICA 4, NERICA 7, ARICA 4 and ARICA 5) to different levels of soil moisture contents at reproductive stage. Open field and screen house experiments were conducted during 2013 and 2014 both in dry season and wet season. Leaf photosynthesis rate, leaf water potential, flowering date and grain yield were compared at reproductive stage under four levels of soil moisture content estimated through tensiometer readings (0 to -5Kpa; -30 to - 40Kpa; -50 to -60Kpa; -75 to -85Kpa). The results showed that, the leaf photosynthesis rate of all the tested varieties decreased with soil water scarcity. Under well-watered condition (control), NERICA varieties yielded from 439 to 497 g.m-2. The grain yield for ARICA varieties ranged from 306 to 337 g.m-2. Under the most severe water deficit, grain yield for NERICA4 and NERICA 7 were significantly (P < 0.05) higher than the other varieties regardless of the years and seasons. Although NERICA 1 had the same trend as the other NERICAs regarding the physiological traits (photosynthesis rate and leaf water potential), it produced lower grain yield under each level of water stress as compared to other varieties. All the entries showed similar trend concerning the delay in days to flowering.
Keywords: ARICA; Agronomical characteristics; NERICA; physiological characteristics; reproductive stage; soil moisture content